ESTABELECIMENTO DE CONSÓRCIOS FORRAGEIROS DE INVERNO SOBRE TIFTON 85 MANEJADO SOB FENAÇÃO - Konradt, Guilherme; Londero, Ana L.; Farias, Joana d. M.; Ost, Henrique J.; Bergoli, Luís M. G.; Maixner, Adriano R.; Uhde, Leonir T.; Sartori, Cesar O.; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo